Optimising ambulance conveyance rates and staff costs by adjusting proportions of rapid-response vehicles and dual-crewed ambulances: an economic decision analytical modelling study. Issue 1 (10th November 2022) - Ridyard, Colin; Smith, Murray; Spaight, Robert; Law, Graham Richard; Siriwardena, Aloysius Niroshan
Abstract : Aim: To model optimum proportions of dual-crewed ambulances (DCAs) and rapid-response vehicles (RRVs) in Ambulance Trusts with a view to generating a policy brief for one Ambulance Trust and a modelling tool for other Trusts on the strategic procurement and allocation of emergency vehicle (EV) resources. Methods: Historical EV assignments for 12 months of emergency calls in 2019 were provided by an NHS Ambulance Trust and analysed for backup, see and treat, and patient to hospital conveyance. Unit costs were derived for paramedics and technicians using Agenda for Change pay rates. Time cycles were assigned for RRV and DCA attendances and unit costs assigned to these. Information was put into a decision analytical model to estimate the costs and numbers of vehicles attending incidents based on relative proportions of available RRVs and DCAs. Results: Of 711 992 calls attended by 837 107 EVs, 514 766 (72.3%) required at least one emergency department conveyance. The rate of conveyance was significantly lower when RRVs arrived first on the scene. 27 883 out of 529 693 (5.3%) DCAs first arriving at an incident required some backup, and this was also factored into the model. Modelling demonstrated high conveyance rates were counterproductive when increasing the relative proportions of RRVs to DCAs. For example, with conveyance rates of 65%, increasing the RRVs increased the cost and numbers of vehicles attending per incident. At lower conveyance rates, however, there was a levelling around 30% where it could become cost-effective to increase the relative proportions of RRVs to DCAs. Conclusion: At current overall conveyance rates, there is no benefit in increasing the relative proportions of RRVs to DCAs unless additional benefits can be realised that bring the conveyance rates down.